Metal-Detecting Rallies: Characterizing the Phenomenon, Understanding the Challenges, and Identifying Strategies for Heritage Protection. Issue 3 (August 2022) - Wessman, Anna; Deckers, Pieterjan; Lewis, Michael; Thomas, Suzie; Nolet, Katelijne
ABSTRACT: Hobby metal detectorists search for archaeological finds as individuals and within groups, the latter being the focus of this article. Such groups come together as "clubs" and "meetings, " but also as part of large, often commercially run events typically known as "rallies." All these activities are attractive to detectorists because they provide them with access to land to search, along with the promise of making interesting (even valuable) discoveries, and they have a social dimension. They are common in England and also well established in several countries in northwest Europe, partly due to changing legislation. Although policies and mechanisms are often in place for collaboration with individual detectorists and even local metal-detecting clubs, larger events (not least, the large-scale commercial rallies increasingly occurring in England) present challenges for professional archaeologists, specifically in relation to the capacity to properly record finds and manage potential damage to the historic environment. To respond appropriately to these changes, a greater understanding of detectorists' events is needed. For this reason, we explore and define the scale, nature, and diversity of group events, relating them to different legislative and cultural contexts in Flanders (Belgium), England (and Wales), and Finland. Subsequently, we outline challenges associated with group events and identify possible ways forward.